'(More) trials and tribulations': the effect of the EU directive on clinical trials in intensive care and emergency medicine, five years after its implementation. Issue 6 (7th June 2010) - Robinson, Katy; Andrews, Peter J D
Abstract : The European Clinical Trials Directive was issued in 2001 and aimed to simplify and harmonise the regulatory framework of clinical trials throughout Europe, thus stimulating European research. However, significant complexity and inconsistency remains due to disparate interpretation by EU member states. Critical care research has been particularly impacted due to variable and often restrictive consenting procedures for incapacitated subjects, with some countries requiring a court-appointed representative, while others recognise consent from family members and occasionally professional representatives. Furthermore, the absence of a waiver of consent threatened to put an end to emergency research in Europe and was met with varied responses. Approval procedures by ethics committees are equally inconsistent, particularly those relating to provision of a single opinion for multi-centre trials. Although evidence is somewhat mixed, this complexity as well as a general increase in administrative and financial burden following the Directive has been shown to cause a reduction in clinical trial activity in Europe, particularly academic trials. We aim to clarify some of these inconsistent procedures, particularly those relating to informed consent of incapacitated subjects, as well as discussing some general weaknesses and possible improvements of the Directive ahead of its planned revision in 2011.